Local-global media images: mediating notions of hope and change among rural youths in Sabah - Haryati Abdul Karim,; Kntayya Mariappan,; Diana Peters,; Suhaimi Salleh,; Mohd Hanafi Jumrah,; Adi Jafar, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This article is about identity and lifestyles formation among rural youths in Sabah through their use of the global-local media images in the midst of living in remote places with little socio-economic activities. The key issue here is to identify to what extent globalization have reached into the lives of rural youths and how these developments have shaped their identity. Findings presented are a combination of quantitative and qualitative data that has been collected over a span of two years beginning 2013. In terms of their media consumption pattern, globalizations have indeed penetrated into the lives of rural youths where almost 70 percent of them are said to have enjoyed a variety of Asian and Western television programs. However, in an interview with 40 informants, out of 38 media images shown, only one girl picked images of an all girls K-pop group as representing who she is. Rather, it was media images of U.S president Barack Obama, Disneyland, Japan and Eiffel Tower that was frequently selected as representing their identity. The reason for this is because these images mediate notions of ‘hope’ and ‘change’ for these youths, who experienced social exclusion. Thus, the main issue concerning globalization, is not about cultural imperialism but how rural youths appropriated global cultures from the media to communicate their local condition in line with Kraidy’s (2002: 17) notion of ‘cultural hybridity’ as a “communicative practice”. Rural youths may appropriate global media content, but it is used to articulate their hope for a better future.